In Vivo Effectiveness of Pleurotus ostreatus in Degradation of Toxic Metabolites of Filamentous Fungi Such as Aflatoxin B1 and Zearalenone - Agnieszka Zapaśnik; Marcin Bryła; Adrian Wojtczak; Barbara Sokołowska (Metabolites)
Background/Objectives: Mycotoxins, secondary metabolites synthesized by filamentous fungi, have been classified as dangerous substances and proven to be carcinogenic, as well as to have genotoxic, nephrotoxic, hepatotoxic, teratogenic, and mutagenic properties. Despite numerous trials to develop an effective and safe-for-human-health method of detoxification, there is still a high risk associated with the occurrence of these toxins in food and feed. Biological methods of food preservation are an alternative option to conventional chemical and physical methods, characterized by their less negative impact on human health as well as their high efficiency against filamentous fungi and other foodborne pathogens. Mycoremediation is a new biotechnique based on the capability of fungi to detoxify matrices from various pullulans. Ligninolytic enzymes produced by white rot fungi (WRF) characterize a high efficiency in the degradation of various mycotoxins. Methods: In our study, Pleurotus ostreatus, as a representative of WRF, was cultivated on a medium contaminated by AFB1 and ZEN (mushroom substrate and maize) in a few variants of concentration. After the cultivation, medium and fruiting bodies were collected and analyzed with the usage of HPLC and LC/MS methods. Results: The reduction oscillated between 53 and 87% (AFB1) and 73 and 97% (ZEN) depending on the initial concentration of toxins in the medium. Grown fruiting bodies contained insignificant amounts of both toxins. Conclusions: These findings confirm the potential of P. ostreatus as an effective biological agent for reducing mycotoxins in contaminated medium, highlighting its applicability in developing sustainable and safe methods for detoxification.